Cervical and scapular instability in subjects with temporomandibular disorder - Vieira, Maryllian de Albuquerque; Araújo, Maria das Graças Rodrigues de; Antonino, Gabriel Barreto; Tenório, Angélica da Silva; Paiva, Maria das Graças; Ferreira, Ana Paula de Lima (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Temporomandibular disorder (TMD) is a set of disorders involving the masticatory muscles, the temporomandibular joint (TMJ) and/or the associated structures. Objectives: To evaluate the occurrence of cervical and scapular instability in subjects with TMD. Methods: A total of 22 patients participated in the study, being 11 of them with TMD, selected using the RDC/TMD criteria, and 11 in the control group. The stabilization capacity of the neck muscles was evaluated through StabilizerTM and the muscles of the shoulder girdle through specific tests. Cervical mobility data from both groups were provided using the accelerometer while for cervical disability was used the Neck Disability Index (NDI) questionnaire. Results: Cervical instability was higher in the TMD group (20.36 ± 3.2) than in the control group (28.54 ± 0.8), revealing significant difference (p= 0.03). The highest percentages of scapular stabilization tests were found in subjects with TMD, (n= 9; 81.81%) when compared with control subjects (n= 5; 45.45%). The NDI results showed that the TMD group presented mild cervical incapacity (11.18 ± 2) and the control presented no disability (2.27 ± 0.4; p= 0.001). Conclusion: Cervical disability, and cervical and scapular instability were more frequent in subjects with TMD.